Synchronization between arterial blood pressure and cerebral oxyhaemoglobin concentration investigated by wavelet cross−correlation - Rowley, A; Payne, S; Tachtsidis, I; Ebden, M; Whiteley, J; Gavaghan, D; Tarassenko, L; Smith, M; Elwell, C; Delpy, D (2007)
Wavelet cross-correlation (WCC) is used to analyse the relationship between low-frequency oscillations in near-infrared spectroscopy (NIRS) measured cerebral oxyhaemoglobin (O(2)Hb) and mean arterial blood pressure (MAP) in patients suffering from autonomic failure and age-matched controls. Statistica